Emphysematous prostatitis combined with a liver abscess caused by Klebsiella pneumoniae - Kim, Ji Young; Ahn, Ke Ryun; Han, Sang Won; Baek, Hae Ri; Lee, Eun Ji; Lee, Chan Bok; Kim, Eun Seok (Infection & chemotherapy, 2011)
Emphysematous prostatitis is a rare condition that is characterized by gas and abscess accumulation in the prostate. This uncommon but serious disease requires special attention because of its nonspecific presentation such as dysuria, frequency,urgency, fever, acute urinary retension and/or perineal pain. We report here on a case of emphysematous prostatitis that was combined with a liver abscess caused by Klebsiella pneumoniae. A 55-year-old man was admitted due to a 3-day history of urinary retention with a febrile sensation. He had histories of liver cirrhosis and uncontrolled diabetes mellitus. After blood and urine cultures, levofloxacin 500mg was started intravenously. On the third hospital day, he displayed septic shock. The kidneys-ureters bladder (KUB) X-ray showed pockets of air-accumulation in the lower pelvic cavity, and abdominopelvic computed tomography (CT) with contrast enhancement taken on the third day showed a 5-cm liver abscess with an emphysematous prostate. Intravenous antibiotics was changed to metronidazole 500 mg q.i.d. and cefotaxime 2 g t.i.d. On the sixth day, transurethral resection and drainage were performed under spinal anesthesia. However, the postoperative bleeding continued and hypovolemic shock persisted, which then provoked multiorgan failure. The patient died on the 11th hospital day. K. pneumoniae was cultured from the liver abscess aspirate, blood and prostatic tissue, and the bacteria were sensitive to both levofloxacin and cefotaxime. Emphysematous prostatitis is a difficult to diagnose because of its rarity and nonspecific symptoms. A delayed diagnosis can cause high mortality and morbidity, so making a prompt clinical diagnosis of this condition is essential. Appropriate antibiotics with early adequate incision and drainage are also needed. KCI Citation Count: 1